(untitled) (Bangladesh Journal of Medical Science, 2020)
Foreign body in the ear including beads and seeds is not uncommon in children. Tick also has been a common aural foreign body especially in tropical climate countries. Although in older cooperative children it can be attempted in the clinic setting, most of paediatric aural foreign bodies require general anaesthesia. In addition, a general practitioner setting may impose additional limitations. The available instruments and experience maybe be different from a tertiary referral centre. We report a case of a 3-year-old child with left ear pain for 4 days associated with loud crying when the pinna was touched. It has been worsening until the cry became continuous. The mother was quite hesitated to bring the child to hospital because of the lockdown situation. She sought nearby general practitioner where the engorged tick was removed without any complication in that clinic alone. Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 82-S 84